THE EFFECT OF BIRTH BALL ON PAIN RELIEF IN PARTICULAR WOMEN IN THE IST ACTIVE PHASE IN SPACE BANCAR COMMUNITY HEALTH CENTER - Wijayanti, Erna Eka; Fatmawati , Aryani Dewi (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2022)
was to determine the effect of the Birth Ball on reducing pain in women giving birth during the first active phase in the delivery room at the Bancar Health Center. This type of research used a quasi-experimental design with a two group pretest posttest design. The population of all mothers giving birth from January to February 2022 is 55 respondents, with a sample of 16 respondents as the intervention group and 16 as the control group. Simple random sampling technique. Analysis of this data uses the independent sample T-Test if the data is normal, if the data is not normal using the Mann Whiteney U-Test. SOP Birth Ball and Visual Analog Scale instruments. The results of this statistical test are based on independent sample T-Test decision making with Asymp values. Sig. (2-tailed) 0.012 < 0.05 which means the hypothesis is accepted. There is an influence of the Birth Ball on reducing pain in women giving birth during the first active phase in the birthing room of the Bancar Health Center. This research can be used as a reference in adding information to provide information and education regarding the implementation of birthball therapy for mothers giving birth during the first active phase.